Procedure for Storing Seeded Cotton in a Cotton Center and a Cotton Factory - Karimullaeva M. U.; Bekniyazov Sh. (International Journal on Integrated Education, 2022)
Enterprises of our republic to increase competitiveness and reach the international market 1SO 9000 series quality management system based on international standards the number of people interested in implementation is increasing. Quality Tenders for the introduction of the management system of enterprises participation, improvement of the management system, production optimization of processes and development of cooperation environment gives opportunities.